Implicature in students’ perception towards language learning - Mansor, Nur Farraliza; Abd Rahim, Normaliza (Serials Publications, 2017)
The study focuses on university students' perception towards language learning in the classroom. The objectives of the study were to identify and discuss the students' perception towards language learning in the classroom. A class of ten university focus group students involved in this study. The focus group subjects volunteered for the study. The subjects were interviewed based on their perceptions towards language learning in the classroom. The extracts from the interviews were analysed by using implicature from Brown & Yule's (1983) theory of discourse analysis where it is the aspect of meaning that a speaker conveys, implies, or suggests without directly expressing. The results of the study revealed that the subjects preferred hands-on activities in language learning classroom due to active participation from all students. Besides that, the results also revealed that the subjects preferred small group discussion that involved digital media. It is hoped that further studies will focus on students' perception towards language learning that involved different types of tools in the classroom.